A Study on the Role of Tofacitinib Among Patients Treated with Alopecia Areata - Asma Javed Kiyani, Huma Afzal Shaikh, Urooj Mirza, Sobia Awan, Alina Saqib, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the efficacy of Tofacitinib in patients with Alopecia Areata. Methods: This interventional study was conducted at Department of Dermatology, Fauji Foundation Hospital Rawalpindi and Cantonment General Hospital Rawalpindi from May, 2022 to October 2022 on 60 patients having hair loss on scalp >50%. Patients were administered with Tofacitinib 5mg BD for 24 weeks. Improvement was assessed by change in the Severity of Alopecia Tool (SALT) score from the baseline. Results: This study was conducted on 60 patients having Alopecia areata. The age of the patients was 33.70±8.69 years. Patients with Alopecia areata 82.9% had >50% change in SALT score, while patients having Alopeciatotalis, 75% showed >50% change in SALT score and patients having Alopeciauniversalis 66.7% showed >50% change in SALT score. Conclusion: From was study we conclude that tofacitinib is an effective treatment for patients with Alopecia areata. Keywords: Alopecia Areata, Tofacitinib, Efficacy